Integrated farming system approach for enhanced farm productivity, climate resilience and doubling farmers’ income - SINGH, V K; RATHORE, S S; SINGH, R K; UPADHYAY, PRAVIN K; SHEKHAWAT, KAPILA (The Indian Journal of Agricultural Sciences, 2020)
Indian agriculture is plagued by several complex challenges like declining factor productivity, poor resource use efficiency, lesser share in Indian economy (14.4%); high dependence of population on agriculture and allied sectors (52%); more thrust on annual cereal crop production etc. Nearly, 86% of the Indian farmers are small and marginal (